Identifying atheroprotective fruits and vegetables by Mendelian Randomization analysis - Yang, Shenji; Cao, Zhikang; Liu, Huidong; Li, Zhipeng; Nie, Shaoping; Xie, Mingyong (Frontiers in Nutrition, 2024)
Background: Fruits and vegetables (FVs) are widely believed to mitigate the risk of atherosclerosis (AS). However, the causal relationships between specific FVs and AS risk factors remain unclear. Methods: This study performed two-sample Mendelian Randomization (MR) analysis to infer the causality of the intake of 28 kinds of FVs with AS, as well as its risk factors including blood low-density lipoprotein cholesterol (LDL-C), triglycerides (TG) and Creactive protein (CRP). GWAS genetic data for these exposures and outcomes were extracted from the IEU open GWAS project. Heterogeneity was evaluated using both Inverse Variance Weighted (IVW) and MR-Egger methods. MR-Egger regression was specifically deployed to detect potential pleiotropy. Furthermore, a "leave-one-out" sensitivity analysis was conducted to determine the impact of each individual single nucleotide polymorphism (SNP) on the combined outcome. Results: The analysis confirms a causal relationship between total fruit consumption and reduced levels of LDL-C (OR=0.911, p=0.007) and CRP (OR=0.868, p=0.008). Similarly, total vegetable intake is also causally associated with a reduction in CRP levels (OR=0.858, p=0.018). Specifically, garlic intake exhibits the most significant causal relationship with reduced risk of AS (OR=0.985, p=0.036) and also causally associated with lower levels of LDL-C and TG. Berry (OR=0.929, p=0.010) and potato (OR=0.957, p=0.020) intake both display a significant causal negative association with TG levels, while peach/nectarine consumption is significantly associated with reduced CRP levels (OR=0.913, p=0.010). Conclusion: This is the first MR study that systemically examined the causality between commonly consumed FVs and AS. Our findings highlight the atheroprotective effects of various FVs, particularly garlic, on cardiovascular health and the importance of tailored nutritional recommendations to prevent AS.